Acupuncturing of myofascial pain trigger points for the treatment of knee osteoarthritis: A systematic review and meta-analysis. Issue 8 (25th February 2022) - Lin, Xingzhen; Li, Fei; Lu, Hualong; Zhu, Manhua; Peng, Tian Zhong
Abstract: Background: Osteoarthritis of the knee is one of the major disorders leading to social dysfunction, economic loss and social development. This study was conducted to systematically evaluate the efficacy and safety effectiveness of acupuncture inactivation of myofascial pain trigger points in the treatment of osteoarthritis of the knee. Methods: Randomized Controlled Trials (RCTs) on the treatment of knee pain were searched by computer from PubMed, The Cochrane Library, China journal full-text database (CNKI), Chinese biomedical literature database (CBM), China academic journal database (Wanfang Data) databases from the date of creation to December 2021, and the data were analyzed by Reman 5.3 software for data analysis. Results: A total of 724 patients from 9 RCTs were finally included, and the results of meta-analysis showed that the acupuncture myofascial pain trigger point group was better than the control group in terms of total effective rate, cure rate, VAS score, Lysholm score, and WOMAC score. Conclusion: The efficacy and safety of acupuncturing myofascial pain trigger points in the treatment of knee osteoarthritis is positive, but due to the limited number of literature included in this study and the low quality of the included literature, there is still a need for high-quality and large sample size RCTs for the analysis of this treatment option.